Effect of glyphosate on the sprouting of Cyperus rotundus L. tubers - Doll, Jerry D.; Piedrahíta Castañeda, Wilson (Wiley, 1982)
Post‐emergence applications of glyphosate [N‐(phosphonomethyl)glycine] have been shown not to eradicate purple nutsedge (Cyperus rotundus L.) in the field. It was not known if this was due to failure to control emerged plants or if dormant tubers produced new plants after application. Studies with individual plants were conducted in screenhouse facilities to determine the effects of glyphosate rate, time for translocation, area of foliage treated, and shade on the sprouting ability of tubers attached to treated plants. Rates of 1.5–2.0 kg/ha glyphosate inhibited tuber sprouting; 72 h were required for complete translocation at 1.0 kg/ha whereas 36 h were sufficient at 2.0 kg/ha. Treating less than all of the foliage reduced foliar control and increased tuber sprouting. Shading treated plants reduced control of the foliage but did not affect glyphosate translocation to the tubers. These studies showed that glyphosate kills C. rotundus foliage and the tubers attached to treated plants. Therefore, regrowth after glyphosate application under field conditions is due to dormant tubers which sprout after treatment.